The specialization of forensic areas as a key factor in the dignified treatment of victims found in clandestine graves - Ruiz Canizales, Raúl; Pichardo Hernández, Juan Alberto; Campos Reyes, Karen (DIXI, 2024)
The objective of this article is to delimit, through a critical analysis, how a specialized interdisciplinary — and even transdisciplinary — strategy in the forensic area, focused on the search and recovery of remains of victims found in clandestine graves, generates favorable conditions for a dignified treatment of these remains. It has been found that the referred forensic work has been carried out independently, or if you will, in a unidisciplinary manner, in which the consequent lack of coordination has generated, as a result, confusion regarding the information on the remains of victims of disappearance. It is concluded that the phenomenon of clandestine graves, in a global manner, has given rise to many questions to which answers are required in a scientific manner and with well-defined methods that would necessarily have to be the result of this multi- and transdisciplinary interaction.
Keywords: Dignity; specialization; clandestine graves; human remains; victims